Cutaneous lesions associated with dual infection caused by canine distemper virus and orthopoxvirus in a domestic cat. Issue 5 (19th July 2013) - Wiener, Dominique J.; Welle, Monika M.; Origgi, Francesco C.
<x xml:space="preserve">Abstract</x> Background Within the context of an increased epidemiological pressure caused by canine distemper virus (CDV) in Switzerland together with a potential re‐emergence of endemic pathogens such as orthopoxviruses (OPXV), dual infections are possible among susceptible species. Objective To describe a case of concurrent CDV and OPXV infection in a cat. Animal A 5‐year‐old, neutered male cat was presented with erythema, crusts and ulcerations around the left eye. High‐grade pruritus and a severe conjunctivitis were also present. Methods Formalin‐fixed skin biopsy samples were obtained from lesional skin. Histopathology, CDV immunohistochemistry and CDV and OPXV RT‐PCR were performed. Results Histopathological examination showed severe epidermal necrosis extending to the follicular walls and a dermal infiltration, predominantly eosinophilic. Intranuclear and intracytoplasmic eosinophilic inclusion bodies were visible in the wall of affected hair follicles, with occasional formation of syncytia. The RT‐PCR revealed the contextual presence of both CDV and OPXV. Scattered cells stained positive for CDV by immunohistochemistry. Conclusion and discussion Dual infections with CDV and OPXV, although rare, may occur and represent additional differential diagnoses for ulcerative skin lesions in cats.